Фитохимическое исследование разных видов табака - Кущугулова, А.М. (My University, 2013)
In this paper, the object of the study were samples of cigarettes (tobacco) – from the Latin. Nicotiána.A - Bond Street Original Selection (strong), B - Bond Street Classic Selection (weak), C - RÖSSLI 15 (Spanish cigars, made in Germany). The work is devoted to phytochemical analysis of different types of tobacco. In this paper we define the qualitative and quantitative content of some of the biologically-active substances (alkaloids, tannins, organic acids and vitamin C).